Mitigating Anxiety in Oral Assessment - Rimmer, Wayne (St Andrews Journal of International and Language Education, 2025)
English for Academic Purposes (EAP) is often characterised as a high-stakes environment, not least because of the role of assessment. While good EAP provision embraces assessment, it would be naïve to claim assessment is always welcomed by students. Particularly if positioned as a gatekeeper and enforcer of standards, assessment can bring anxiety. Since oral assessment often plays a dominant role in EAP, this practice-focused paper examines anxiety within speaking tasks. Its purpose is to highlight anxiety as a reliability risk in oral assessments and present strategies for student anxiety management (SAM). The recommendation is that EAP practitioners incorporate SAM strategies into their provision. To illustrate, three SAM strategies are presented within the context of oral assessment: test-wiseness (negotiating the assessment process via strategies independent of the actual assessment construct), self-regulation (student management of their learning), and emotional regulation (control over the emotions feeding anxiety). The conclusion is that while no panacea, SAM is likely to remain relevant so long as assessment is prominent in the EAP curriculum. Furthermore, the provision of SAM serves as a reminder to practitioners of their ethical obligation to mitigate anxiety in all forms of assessment.